Formen und Funktionen der Intertextualitaet im Prosawerk von Anton Čechov - Smola, Klavdia (Slavistische Beitraege, 2004)
In this monograph an attempt is made to elucidate and systematize selected intertextual references in the prose book of Anton Čechovs with the help of concepts, categories and models developed in the field of intertextuality theory. It is not only about the determination of new texts, but sometimes primarily about a more sophisticated investigation of the intertextual signals, which are questioned on their specific position, form and function in the structure of the text. In this way, a more precise intertextual analysis of individual prose works by Čechov is suggested. Based on the study of some early short stories, we first discuss such types of second-degree texts, such as affirmative imitations, parodies, and counterfactures. This reveals an alternative to the predominantly parodic intertextuality of the early Čechov. Finally, attention is drawn to the varieties of fictional literary reception in the later work of Čechov.